Optimizing injection pressure for diesel engines fueled with waste cooking oil biodiesel blends - Achmad Aminudin; Doni Setyo Pamungkas; Imam Basuki; Nanang Romandoni; Nur Ihda Farikhatin Nisa; Kelvin Dwi Wardana (Jurnal Polimesin, 2026)
This study examines the effects of used cooking oil biodiesel and injection pressure on diesel engine performance and emissions. Highlights the combined effects of injection pressure and biodiesel blends. The fuel mixtures used were Pertamina Dex (B0), B50 (50% biodiesel), and B65 (65% biodiesel), with injection pressures of 160, 170, and 180 bar. Tests were conducted on a Dongfeng S195 diesel engine with a load of 1000–5000 watts. The parameters tested included fuel characteristics (density, viscosity, flash point, and calorific value), Brake Specific Fuel Consumption (BSFC), Brake Thermal Efficiency (BTE), and exhaust gas opacity. The results show that injection pressure plays a critical role in optimizing biodiesel combustion. The B65 blend at an injection pressure of 170 bar produced the lowest BSFC of 279.30 g/kWh and a high BTE of 25.54%, approaching that of pure diesel. In terms of emissions, the lowest opacity value of 5.88% was achieved with the B65 blend at 180 bar. These findings demonstrate that an optimal injection pressure, particularly 170 bar, can significantly improve fuel efficiency and combustion performance of high-percentage biodiesel blends while reducing exhaust smoke. Thus, used cooking oil biodiesel can improve fuel safety and efficiency as well as reduce emissions, provided it is combined with optimal injection pressure.